ANALISIS KOMPARATIF DENGAN METODE ALTMAN Z-SCORE DAN ZMIJEWSKI DALAM MEMPREDIKSI KEBANGKRUTAN PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BEI PERIODE 2018-2021 - ., Krisnawan; Noviarti (Jurnal Manajemen, 2023)
This study aims to predict potential bankruptcy. The samples in this study were six Transportation and Logistics companies listed on the Indonesia Stock Exchange for the period 2018-2021. This study uses a quantitative descriptive research design and uses the Wilcoxon Signed Rank Test. The results of this study indicate a significant difference between the Altman Z-Score and Zmijewski methods. The Zmijewski method has the highest calculation accuracy rate, which is 100%. Therefore, the Zmijewski method is the most effective method for predicting potential bankruptcy in Transportation and Logistics sector companies.